Hubungan Inisiasi Menyusu Dini (IMD) Dengan Keberhasilan Pemberian Asi Eksklusif Pada Bayi Di Wilayah Kerja Puskesmas Tegalrejo - Nahda Husen; Fathiyatur Rohmah (CV. ITTC INDONESIA, 2025)
Exclusive breastfeeding is the best nutrition for infants during the first six months of life, enhancing immunity and preventing mortality due to infections and malnutrition. Global data indicate that exclusive breastfeeding coverage is lower in developed countries compared to low- and middle-income countries. In Indonesia, exclusive breastfeeding coverage remains below the national target of 80% and has continued to decline. Only 52.5% of infants under six months received exclusive breastfeeding in 2021, a decrease from 2019. In the Special Region of Yogyakarta (DIY), Yogyakarta City has not yet reached the exclusive breastfeeding coverage target (73.25%) compared to four other regencies that have exceeded the target. This study aims to examine the correlation between early breastfeeding initiation (IMD) and the success of exclusive breastfeeding among infants in the working area of Puskesmas Tegalrejo, Yogyakarta. The research employed a quantitative approach with a cross-sectional design. The sample consisted of 69 mothers with infants aged 6–12 months. Data were collected using questionnaires and analyzed using the Chi-Square test. The results showed that out of 69 respondents, 51 mothers (73.9%) performed IMD, and 40 mothers (58.0%) successfully provided exclusive breastfeeding. Statistical analysis revealed a significant correlation between IMD and the success of exclusive breastfeeding (p = 0.003).